New Insights in Immunotherapies for Food Allergies. A Path between the Mouse Model and the Allergic Patient - Smaldini, Paola Lorena (2015)
Allergic diseases are the most prevalent immunopathologies worldwide.Nowadays, allergen avoidance is the unique effective treatment for allergic patients. Pre-clinical studies and clinical trials have been successful to provethat immunotherapies may accomplish mucosal mechanisms of allergenspecifictolerance, which are able to revoke the allergic sensitization. Although more than 100 years have elapsed since the first reported procedure achieved in patients sensitive to pollen, the main obstacle in these therapies still remains adverse reactions induced during treatment. The need for further studies is required to explore safe and effective therapeutic protocols. More recently, immunotherapy appears to be an attractive option for patients with food allergy, although it is still experimental. Different strategies were proposed to overcome the concerning adverse effects that compromise safety, effectiveness and compliance with treatments. At this point, translational medicine is a flourish field in the arenas of basic science, applied science, and clinical research. The use of experimental animals may provide new insights to unravel mechanisms that play key roles in desensitization and tolerance induction, and to modify existing protocols or design new therapeutic approaches. The present reviews describes the different immunotherapies that are used in allergic patients, the promising immune interventions that are currently evaluated in clinical trials and the contributions that animal models may provide to improve the quality of treatments.